2018
DOI: 10.1017/s0956796818000011
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of dependent interoperability

Abstract: Full-spectrum dependent types promise to enable the development of correct-by-construction software. However, even certified software needs to interact with simply-typed or untyped programs, be it to perform system calls, or to use legacy libraries. Trading static guarantees for runtime checks, the dependent interoperability framework provides a mechanism by which simply-typed values can safely be coerced to dependent types and, conversely, dependently-typed programs can defensively be exported to a simply-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Dependent Contract Checking. We also plan to explore using GTT's specification of casts in a dependently typed setting, building on work using Galois connections for casts between dependent types (Dagand et al, 2018;Eremondi et al, 2019), and work on effectful dependent types based a CBPV-like judgement structure (Ahman et al, 2016;Pédrot & Tabareau, 2020).…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…Dependent Contract Checking. We also plan to explore using GTT's specification of casts in a dependently typed setting, building on work using Galois connections for casts between dependent types (Dagand et al, 2018;Eremondi et al, 2019), and work on effectful dependent types based a CBPV-like judgement structure (Ahman et al, 2016;Pédrot & Tabareau, 2020).…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…Recently, work on dependent interoperability [Dagand et al 2016[Dagand et al , 2018 has identified Galois connections as a semantic formulation for casting between more and less precise types in a nongradual dependently typed language, and conjectures that this should relate to type dynamism. We confirm their conjecture in showing that the casts in gradual typing satisfy the slightly stronger property of being embedding-projection pairs and have used it to explain the cast semantics of gradual typing and graduality.…”
Section: Related Work and Discussionmentioning
confidence: 99%
“…The programmer knows that as long as vectors are used in vector-expecting code, no crashes can happen, and safety ensures that using a list in a vector operation will always fail gracefully or run successfully. This is significantly different from work on casts to subset types [Tanter and Tabareau 2015] and dependent interoperability [Dagand et al 2018], where the user must explicitly provide decidable properties or (partial) equivalences.…”
Section: Gradual Guarantees For Gdtlmentioning
confidence: 99%
“…Osera et al [2012] present dependent interoperability as a multi-language approach to combine both typing disciplines, mediated by runtime checks. Building on the subset cast framework (reformulated in a monadic setting instead of using axiomatic errors), Dagand et al [2016Dagand et al [ , 2018 revisit dependent interoperability in Coq via typetheoretic Galois connections that allow automatic lifting of higher-order programs. Dependent interoperability allows exploiting the connection between pre-existing types, such as Vec and List, imposing the overhead of data structure conversions.…”
Section: Related Workmentioning
confidence: 99%